NILAI TAMBAH SABUT KELAPA PADA INDUSTRI PENGOLAHAN PT. BERKAT ABADI KORINDO KECAMATAN MATUARI KOTA BITUNG - Aldi Dian Sahputra Menang; Nordy Fritsgerald Lucky Waney; Mex Frans Lodwyk Sondakh (Sam Ratulangi University, 2021)
This study aims to determine the added value of coconut coir in the processing industry of PT. Berkat Abadi Korindo, Bitung City. This research was conducted at PT Berkat Abadi Korindo Bitung City from January to March 2020. The location was determined purposively with the consideration that PT. Berkat Abadi Korindo is the only company that processes coconut coir into â€œFish Netâ€ products in North Sulawesi. The type of data used in this study is primary data obtained through direct interviews with company owners using a list of data requirements that have been prepared as well as direct observations about conditions in the field during the analysis period. The research data were analyzed descriptively and quantitatively using added value analysis. The results of this study indicate the coconut coir processing industry of PT. Berkat Abadi Korindo, Matuari Sub-District, Bitung City provides added value of more than 0 or Rp. 2,331.14 from every 1 kg of coconut husk to 0.16 kg of